Empowering Santri Ponpes As-Sunniyyah dalam Pembuatan Buku Kunci Nahwu - Kafi, Fina Aunul; Mutayasiroh, Siti Khamidatul (INAIFAS Press, 2023)
The female students at Ponpes Assunniyyah Kencong Jember have potential in Arabic grammar. Their attainable needs to be developed, so that they are able to utilize their abilities to produce productive work. This community service activity aims to assist them in compiling the Nahwu Key book, which is the essence of the Nahwu book for the basic level. To achieve this goal we use the ABCD approach. After the mentoring, they succeeded in compiling a basic level book of Nahwu Keys that they could need to benefit the Arabic language enthusiasts around them. Empowering the potential of the female students of Ponpes Assunniyyah can foster their skills in practical book preparation according to their potential.